Covid-19 and rapid adoption and improvisation of online teaching: curating resources for extensive versus intensive online learning experiences. Issue 4 (1st October 2020) - Bryson, John R.; Andres, Lauren
ABSTRACT: The COVID-19 pandemic closed university campuses forcing rapid improvisation and adoption of online teaching. This paper explores the experience of converting three modules from proximate to online learning delivery in March and May 2020. This process was facilitated by reflective practice to support a process of improvisation as a buffering response to the pandemic. This paper distinguishes between the development of Distance Learning programmes compared to rapid adoption of online learning. Shifting to complete online teaching involves a process by which the lecturer's role transitions towards the curation of online and offline student experiences. This includes facilitating and blending extensive and intensive online learning experiences. Extensive involves the selection and curation of online learning support bundles. This requires the creation of learning roadmaps to facilitate student learning. Intensive revolves around online engagement between academics and students and takes two forms: shallow as involving a limited dialogue with students and deep which involves a co-creation process between students and lecturers. Online learning provides opportunities to adapt learning experiences in real-time. The paper evaluates the shift to online practice from the students' and academics' perspectives.